Electoral systems and the balance of consumer-producer power - Chang, Eric C. C., 1971- (New York : Cambridge University Press, 2011)
'This book investigates the effects of electoral systems on the relative legislative and, hence, regulatory influence of competing interests in society. Building on Ronald Rogowski and Mark Andreas Kayser's extension of the classic Stigler-Peltzman model of regulation, the authors demonstrate that majoritarian electoral arrangements should empower consumers relative to producers. Employing real price levels as a proxy for consumer power, the book rigorously establishes this proposition over time, within the OECD, and across a large sample of developing countries. Majoritarian electoral arrangements depress real prices by approximately ten percent, all else equal. The authors carefully construct and test their argument and broaden it to consider the overall welfare effects of electoral system design and the incentives of actors in the choice of electoral institutions'--
Machine generated contents note: 1. Introduction; 2. Electoral systems and consumer power: theoretical considerations; 3. Electoral systems and real prices: panel evidence for the OECD countries; 4. Electoral systems and real prices around the world; 5. A closer look: case studies and mechanisms; 6. Socio-economic origins of electoral systems; 7. Discussion and conclusion.
Includes bibliographical references and index.
Keywords: Elections -- Economic aspects; Voting -- Economic aspects; Consumers; Prices; Comparative government